Microstructure and sulfonation of dual monomer‐grafted polypropylene nonwoven fabrics. Issue 3 (25th July 2019) - Tao, Ran; Pang, Qinyu; Xu, Tao; Xu, Luyan; Yang, Xuhong; Zhu, Xinsheng
ABSTRACT: The sulfonation of styrenic polymers often needs harsh reaction conditions, such as concentrated sulfuric acid and elevated temperature. The awkward situation is handled by grafting copolymerization of polar and nonpolar monomers, and essentially the surface wettability between sulfonating agent and matrix polymer is circumvented in the study. Two pairs of dual monomers, glycidyl methacrylate (GMA)‐acrylic acid (AA), styrene (St)‐acrylic acid (AA), were grafted onto polypropylene nonwoven fabrics (PP) using thermal polymerization, and the resulted fabrics were further sulfonated using sodium sulfite and sulfuric acid, respectively. The microstructure of the modified fabrics was characterized by infrared spectroscopy and scanning electron microscopy. The ion exchange property was verified by copper (II) removal from aqueous solution, and its reutilization was carried out in electrochemical desorption process. The results show that hydrophilic and active monomer AA speeds grafting and sulfonation, but overload of AA will deteriorate copolymerization of GMA, and switch copolymerization chain component due to acylation with benzene ring. Although interfacial compatilizer promotes dual grafting, its overdosing may intensify microphase segregation of the grafting polymers owing to emulsification. The resultant granular polymers will be drained off during functionalization and reutilization processes. The ion exchange fabrics can be applied for treatment of metal ion wastewaters with unique electrochemical desorption feature. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48300. Abstract : Morphology of dual‐monomer grafting and subsequent sulfonation of polypropylene non‐woven fabrics.